2013
DOI: 10.1242/dev.094938
|View full text |Cite
|
Sign up to set email alerts
|

Pdgfra protects against ethanol-induced craniofacial defects in a zebrafish model of FASD

Abstract: Human birth defects are highly variable and this phenotypic variability can be influenced by both the environment and genetics. However, the synergistic interactions between these two variables are not well understood. Fetal alcohol spectrum disorders (FASD) is the umbrella term used to describe the wide range of deleterious outcomes following prenatal alcohol exposure. Although FASD are caused by prenatal ethanol exposure, FASD are thought to be genetically modulated, although the genes regulating sensitivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
157
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(165 citation statements)
references
References 81 publications
8
157
0
Order By: Relevance
“…28,52 However, in our analyses discussed below, we have found that 1% ethanol merely sensitizes embryos to craniofacial defects, 53 differences that may be due to genetic background. Due to the large number of transgenic backgrounds available, new insights are being gained into how ethanol disrupts neural development in zebrafish.…”
Section: Zebrafish Models Of Fasdmentioning
confidence: 67%
See 3 more Smart Citations
“…28,52 However, in our analyses discussed below, we have found that 1% ethanol merely sensitizes embryos to craniofacial defects, 53 differences that may be due to genetic background. Due to the large number of transgenic backgrounds available, new insights are being gained into how ethanol disrupts neural development in zebrafish.…”
Section: Zebrafish Models Of Fasdmentioning
confidence: 67%
“…Pdgfra acts through the PI3K/ mTOR pathway to regulate cell survival, proliferation, and growth, 99,100 and we found that this pathway mediates the pdgfra-ethanol interaction. 53 Pdgfra function is conserved among zebrafish, mice, and human 94,96,97 and, in human, we identified single-nucleotide polymorphisms in PDGFRA and PDGFRB that significantly associated ethanol-induced changes in outer canthal width and midfacial depth, respectively. 53 This suggests that growth factor signaling as a target of ethanol teratogenesis and that studies in animal models can predict gene-ethanol interactions in human FASD.…”
Section: Identifying Gene-ethanol Interactions: the Way Of The Fishmentioning
confidence: 89%
See 2 more Smart Citations
“…For instance, zebrafish pdgfra directs morphogenesis of the craniofacial skeleton, and its activity is sensitive to genetic and environmental perturbations suspected in the etiology of mammalian clefting disorders (Eberhart et al, 2008;McCarthy et al, 2013). Similarly, mutations in murine Pdgfc ligand and Pdgfra receptor result in facial and palate clefts due to both reduced cell proliferation and inadequate migration of neural crest derivatives (Ding et al, 2004;He and Soriano, 2013;Smith and Tallquist, 2010).…”
Section: Introductionmentioning
confidence: 99%